Prevalence Distribution of Fundamental Movement Skills in Children of Tehran Elementary Schools - Hamid Salehi; Mahshid Zarezade (University of Tehran, 2016)
Fundamental movement skills are observable patterns of motor behaviors including locomotor, manipulative, and stability activities. The aim of this study was to assess the gross motor development and the movement skill proficiency in elementary school children in Tehran city. The test of Gross Motor Development-2 (Ulrich, 2000) was administered to 712 children aged between 7 and 11. Performance of each 12 gross motor skills was assessed qualitatively. The percentages of poor/professional and nearly professional (advanced) children were reported by gender and age group. The assessments indicated that the highest percentages of advance level for both genders belonged to sliding and running, but these proportions were generally low in other skills. The percentages of advanced boys were statistically more than the percentages of girls in one locomotor skill (leaping) and two object-control skills (kicking and striking). In three object-control skills (dribbling, kicking and throwing), the percentages of the older advanced children were statistically more than younger ones. It was suggested that more attention should be paid to promote movement skill proficiency in elementary schools.